IMPROVEMENT ABILITY TO KNOWING NUMBER CONCEPTS THROUGH INTERACTIVE VIDEO MEDIA FOR CHILDREN AGED 5-6 YEARS IN PUBLIC KINDERGARTEN PEMBINA 1 PALEMBANG - Syafdaningsih Syafdaningsih (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to improve the ability to knowing number concepts through interactive video media for children aged 5-6 years in Public Kindergarten Pembina 1 Palembang. The method used is a classroom action research method developed by Kemmis and Taggart. The action is carried out in two cycles. Each cycle consists of stages of planning, action, observation, and reflection. Data collection techniques are observation, documentation, and tests. The subject of this study consisted of 20 students aged 5-6 years. Research data analysis was obtained based on increasing the ability to recognize the concept of student numbers from pre-action to cycle II. There are a number of students who get a score with minimum criteria of developing according to expectations (BSH) in the pre cycle of 5 students (25%), the first cycle as many as 9 students (45%), and in the second cycle as many as 16 students (80%). This is evidenced by the achievement of indicators by students in sorting numbers 1-20 and calculating the number of numbers, so that an increase of 35% occurs. The results show that the use of interactive video media can improve the ability to recognize the concept of student numbers